1999
DOI: 10.1007/s004360050636
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Trypanosoma cruzi within tissues from chagasic patients using confocal microscopy with monoclonal antibodies

Abstract: Confocal fluorescence microscopy combined with differential interference contrast imaging of tissues from chagasic patients enabled the unequivocal identification of the parasite Trypanosoma cruzi. Using different monoclonal antibodies that indicate the parasite form and replication stage in conjunction with DNA labelling, specimens derived from distinct clinical forms of the disease were examined. Intracellular amastigote forms of the parasite were clearly detected in heart, brain, skin, lung, and kidney. Div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 23 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Goat anti-rabbit IgG-peroxidase (A6154), goat anti-mouse IgG-peroxidase (A4416) and goat anti-human Alexa Flour 488 (A11013) were from Sigma-Aldrich. Anti- T. cruzi was previously used (Mortara et al, 1999 ).…”
Section: Methodsmentioning
confidence: 99%
“…Goat anti-rabbit IgG-peroxidase (A6154), goat anti-mouse IgG-peroxidase (A4416) and goat anti-human Alexa Flour 488 (A11013) were from Sigma-Aldrich. Anti- T. cruzi was previously used (Mortara et al, 1999 ).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, in situ PCR (Polymerase Chain Reaction) and confocal analyses have shown that even in the chronic phase, tissues are not parasite-free (1118). Several tissues, including the heart and the nervous system, as well as adipocytes, retain amastigote forms that perpetuate the chronic infection (1921). Additionally, Chagas disease may be reactivated during periods of immunosuppression, such as in patients with HIV/AIDS or undergoing immunosuppressive drug therapy (22, 23).…”
Section: Trypanosoma Cruzi Infection Targets Several Tissues In the Hostmentioning
confidence: 99%